Major histocompatibility complex alleles associated with parasite susceptibility in wild giant pandas - Zhang, L (Heredity (Edinb), 2015)
Major histocompatibility complex (MHC) polymorphism is thought to be driven by antagonistic coevolution between pathogens and hosts, mediated through either overdominance or frequency-dependent selection. However, investigations under natural conditions are still rare for endangered mammals which often exhibit depleted variation, and the mechanism of selection underlying the maintenance of characteristics remains a considerable debate. In this study, 87 wild giant pandas were used to investigate MHC variation associated with parasite load. With the knowledge of the MHC profile provided by the genomic data of the giant panda, seven DRB1, seven DQA1 and eight DQA2 alleles were identified at each single locus. Positive selection evidenced by a significantly higher number of non-synonymous substitutions per non-synonymous codon site relative to synonymous substitutions per synonymous codon site could only be detected at the DRB1 locus, which leads to the speculation that DRB1 may have a more important role in dealing with parasite infection for pandas. Coprological analyses revealed that 55.17% of individuals exhibited infection with 1–2 helminthes and 95.3% of infected pandas carried Baylisascaris shroederi. Using a generalized linear model, we found that Aime-DRB1*10 was significantly associated with parasite infection, but no resistant alleles could be detected. MHC heterozygosity of the pandas was found to be uncorrelated with the infection status or the infection intensity. These results suggested that the possible selection mechanisms in extant wild pandas may be frequency dependent rather than being determined by overdominance selection. Our findings could guide the candidate selection for the ongoing reintroduction or translocation of pandas.